Sistem Pakar Diagnosa Penyakit ISPA dengan Metode Forward Chaining - Gusmaliza, Debi; Masdalipa, Risnaini; Yadi, Yadi (Building of Informatics, Technology and Science (BITS), 2022)
The development of computer technology today continues to experience many changes every year, which are often developed by artificial intelligence, such as expert system technology. An expert system is a computer-based application that can match or imitate the ability of an expert used to solve problems that cannot be solved by ordinary people. His knowledge is taken from books, experience and knowledge. Children often experience ISPA disease caused by viruses and bacteria because children's immune systems are still susceptible to being different from adults. This disease usually begins with a hot body temperature accompanied by symptoms such as sore throat or painful swallowing, runny nose, dry cough and others. So that many parents do not know the symptoms of ISPA disease, as for some ways to prevent ISPA disease are diligently washing hands, increasing consumption of foods containing vitamins, exercise. To make it easier for parents to detect ISPA disease, the authors made this study using the forward chaining method, using this method the resulting system is a system that provides a choice of several symptoms then based on the selected symptoms conclusions will be drawn. This ARI disease expert system uses blackbox testing because blackbox testing is a software testing technique that focuses on the functional specifications of the software or system. Blackbox testing is done on each submenu view, input, edit, print, delete data. So that it will produce an expert system to diagnose ISPA in children online